Sensory Characteristics and Content of Hydroxymethyl-Furfural and Polyphenols in Dried Apples and Health-Related Considerations: Life Sciences-Health - Aljilji, Ajka; Mahmutovic, Omer; Prazina, Nedzad; Sejfopapic; Velic, Safet (International Journal of Life Science and Pharma Research, 2022)
Dried apples improve your health owing to their mineral contents. The main function of packaging dried apples is to protect the packaged product from external factors that may affect the contents' physicochemical, mechanical, and sensory changes during the storage period. The study investigates the sensory characteristics and content of hydroxymethyl-furfural and polyphenols in dried apples and health-related considerations. To gratify that aim, the mixed apple sample was calibrated (precise sorting according to the size and color of the apples), selected, washed, and cut into slices. The product is sulfurized with SO2, the procedure takes several hours, and it is immediately introduced into the dryer. The mass is dried in a dryer "Iverak" (Valjevo, Serbia) with warm air at a temperature of max 65 ° C for 15-18 hours. Packaging materials used in the study are: 1. Monomaterial, polyethylene (PE), thickness 95μ m (PE (95) μ m); 2. Combined packaging material, oriented polypropylene metallized (OPP), thickness 20 μ m (OPPmet (20) μ m); 3.Combined packaging material, oriented polypropylene (OPP) / polyethylene (PE) thickness 20 / 50μ m (OPP / PE (20/50) μ m); 4.Combined packaging material, oriented polypropylene metallized (OPPmet) / polyethylene (PE) thickness 20 / 50μ m (OPPmet / PE (20/50) μ m); 5.Combined packaging materials, polyester (PET) / oriented polypropylene metallized (OPP) met / polyethylene thickness 12/38/30 (PET/OPPmet/PE(12/38/30) μ m). The study presents the results of testing in changes of content of hydroxymethyl-furfural (HMF), polyphenols and sensory properties, dried apples packed in different combinations of packaging materials, including PE (95) μ m, OPP met (20) μ m, OPP / PE (20/50) μ m, OPP met / PE (20/50) μ m, PET / OPP met / PE (12/38/30 μ m), considering health issues. The article's findings can make a notable contribution to the knowledge of the thermal kinetics of antioxidant impacts and phenolic content over the production of apple chips.